ANALYSIS OF THE CAPABILITY OF SALES STRATEGIES ON THE PERFORMANCE OF MSMES IN BATAM CITY IN THE FACE OF THE COVID 19 SITUATION - Emi Lestari; Hardi Bahar (Politeknik Negeri Batam, 2021)
MSMEs are part of Indonesia's economic growth. This global pandemic has had a significant impact on all aspects of the world and in fact it is not only in foreign countries, the Indonesian state is also about a tremendous impact on the national economic sector, especially for Micro Enterprises; Small; and Intermediate. In recent years, developments in the MSME sector have had obstacles and weaknesses that are commonly faced by entrepreneurs in terms of improving their business performance, including the lack of a good capital system and the amount and source of capital, lack of managerial ability and skills in terms of operations, limitations in product marketing. products, unfair competition among businesses, and economic pressure which results in a narrow and limited scope of business. With the need to improve business performance in terms of increasing sales, capital, labor, market and profit growth, business actors need to implement a sales strategy in running a business. Therefore, this study aims to determine how the influence of the sales strategy with the sections of Customer Segmentation, Customer Priority and Targeting, Relationship Objectives and Sales Model, and the use of several sales channels on the performance of MSMEs. The population part of the study is all MSMEs in Batam City with sampling using purposive random sampling technique, thus this study took the number of respondents of 101 samples obtained in data collection. The data analysis in this study used descriptive statistical analysis and inferential statistics, namely Structural Equation Modeling Patrial Least Square (SEM-PLS) using the smart-pls 3.0 application. The results of this study indicate that the sales strategy with the characteristics of the use of several sales channels and customer segmentation has a significant effect on the performance of the UMKM, while the sales strategy with the characteristics of Customer Priority & Targeting and relationship objectives & the sales model have no effect on the performance of the UMKM.